2015
DOI: 10.1177/1555412015595298
|View full text |Cite
|
Sign up to set email alerts
|

A Realm of Mere Representation? “Live” E-Sports Spectacles and the Crafting of China’s Digital Gaming Image

Abstract: This article addresses the proliferation of images and appearances in the realm of e-sports culture in urban China. The author's findings are based upon ethnographic research and participant observation of e-sports audience members, teams, and tournaments, including the 2010 E-sports Champion League tournament in Beijing, the 2012 and 2013 World Cyber Games Festivals in Kunshan, and a 2014 Starcraft II tournament in Shanghai. A comparison of these events leads the author to argue that live e-sports events in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 16 publications
0
31
0
2
Order By: Relevance
“…The concept of digital nationalism has effectively infiltrated the realm of eSports culture in China thanks to non-stop endeavours of the state. Szablewicz ( 2016 , 2020 ) addressed the proliferation of images and appearances in live eSports events in China and concluded that these events, along with the active participation of the Chinese youth, are less about spectatorship and not merely about fandom and playing per se. The combination of these elements has created a spectacle that reasonably represents a meticulously crafted vision of Chinese politics and consumer culture.…”
Section: Why East and Southeast Asia Matter?mentioning
confidence: 99%
“…The concept of digital nationalism has effectively infiltrated the realm of eSports culture in China thanks to non-stop endeavours of the state. Szablewicz ( 2016 , 2020 ) addressed the proliferation of images and appearances in live eSports events in China and concluded that these events, along with the active participation of the Chinese youth, are less about spectatorship and not merely about fandom and playing per se. The combination of these elements has created a spectacle that reasonably represents a meticulously crafted vision of Chinese politics and consumer culture.…”
Section: Why East and Southeast Asia Matter?mentioning
confidence: 99%
“…This STEMification is not without some empirical basis: even in our limited data set, the majority of varsity programs we learned about were either housed within or institutionally positioned alongside Computer Science (CS) departments (with their own long-standing history of gender-based exclusions; see Master et al, 2016), and CS majors are often seen as the obvious source for recruiting talent. But equally agential to this STEMification is the larger technocultural imaginary in which esports thrives: representative of how sport itself is changing to adapt to our increasingly hybridized, digitized realities (Hutchins, 2008), and held up as emblems of a country's technological and economic superiority (Szablewicz, 2016).…”
Section: Title IXmentioning
confidence: 99%
“…27 Live eSports competitions are presented as media spectacles that nurture the ideal patriotic citizen, just like any other major events-for instance, the Olympics or the national games; accordingly, eSports has become a platform to display carefully crafted nationalism and China's soft power. 28 Hence, we have witnessed seemingly contradictory policies toward eSports and online gaming: regulations aiming at minimizing negative social impact and gaming addition 29 while encouraging a pragmatic nationalism that sees Chinese eSports players winning in international competitions. As Hjorth and Chan have noted, both Korea and Japan have successfully casted themselves as the center of Asian games market and leaders of "techno-cool."…”
Section: The Rise Of the Esports Central Kingdommentioning
confidence: 99%